Helminth Infections and Cardiovascular Diseases: Toxocara Species is Contributing to the Disease - Zibaei, Mohammad (Current Cardiology Reviews, 2017)
Toxocariasis is the clinical term used to describe human infection with either the dog ascarid Toxocara canis or the feline ascarid Toxocara cati. As with other helminths zoonoses, the infective larvae of these Toxocara species cannot mature into adults in the human host. Instead, the worms wander through organs and tissues, mainly the liver, lungs, myocardium, kidney and central nervous system, in a vain attempt to find that, which they need to mature into adults. The migration of these immature nematode larvae causes local and systemic inflammation, resulting in the “larva migrans” syndrome. The clinical manifestations of toxocariasis are divided into visceral larva migrans, ocular larva migrans and neurotoxocariasis. Subclinical infection is often referred to as covert toxocariasis. One of the primary causes of death all around the world is cardiovascular disease that accounted for up to 30 percent of all-cause mortality. Cardiovascular disease and more precisely atherosclerotic cardiovascular disease, is predicted to remain the single leading cause of death (23.3 million deaths by 2030). A-quarter of people presenting the disease does not show any of the known cardiovascular risk factors. Therefore, there is considerable interest in looking for novel components affecting cardiovascular health, especially for those that could improve global cardiovascular risk prediction. This review endeavours to summarize the clinical aspects, new diagnostic and therapeutic perspectives of toxocaral disease with cardiovascular manifestations.
Keywords: cardiovascular